Poverty Reduction Policies and Practices in Developing Asia - Heshmati, Almas; Maasoumi, Esfandiar; Wan, Guanghua; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2015)
This book looks at the major policy challenges facing developing Asia and how the region sustains rapid economic growth to reduce multidimensional poverty through socially inclusive and environmentally sustainable measures. Asia is facing many challenges arising from population growth, rapid urbanization, provision of services, climate change and the need to redress declining growth after the global financial crisis. This book examines poverty and related issues and aims to advance the development of new tools and measurement of multidimensional poverty and poverty reduction policy analysis. The book covers a wide range of issues, including determinants and causes of poverty and its changes; consequences and impacts of poverty on human capital formation, growth and consumption; assessment of poverty strategies and policies; the role of government, NGOs and other institutions in poverty reduction; rural-urban migration and poverty; vulnerability to poverty; breakdown of poverty intochronic and transitory components; and a comparative study on poverty issues in Asia and other regions. The book will appeal to all those interested in economic development, resources, policies and economic welfare and growth.
Acknowledgments -- Chapter 1: Introduction and Summary to Poverty Reduction Policies and Practices in Developing Asia -- Part One: Poverty Alleviation with Microfinance -- Chapter 2: Poverty Alleviation with Microfinance: Bangladesh Evidence -- Chapter 3: Does Microcredit Help the Poor and Financially Marginalized Communities? Experience of Pakistan -- Part Two: Climate Change, Disaster Management and Poverty Reduction -- Chapter 4: Climate Change, Agricultural Production and Poverty in India -- Part Three: Urban Poverty Reduction Policies -- Chapter 5: Urban Poverty in Developing Asia$1 (BDichotomy between the Income and Non-Income Dimensions: Are We Not Grossly Underestimating Its Incidence? -- Chapter 6: Housing Poverty and Inequality in Urban India -- Part Four: Rural Poverty Reduction Policies -- Chapter 7: Evaluation of the Policy of Crop Diversification as a Strategy for Reduction of Rural Poverty in India -- Chapter 8: Conflict and Livelihood Decisions in the Chittagong Hill Tracts of Bangladesh -- Part Five: Dimensions of Poverty and its Reductions -- Chapter 9: Decomposing Spatial Inequality in Sri Lanka: A Quantile Regression Approach -- Chapter 10: Non-Income Dimensions, Prevalence, Depth and Severity of Poverty: Spatial Estimation with Household Level Data in India -- Chapter 11: Is Poverty Comparable Across Varying Size of Population Among Indian States? -- Part Six: Sustainability in Poverty Reduction -- Chapter 12: The Significance of Foreign Labour Migration and Land for Poverty Reduction in Nepal -- Chapter 13: Does Poverty Alone Keep Children Out of School? The Case of Children under Kinship Care in the Philippines -- Part Seven: Alleviation of Poverty in Asia and the Pacific -- Chapter 14: Economic Class and Labour Market Segregation: Poor and Middle Class Workers in Developing Asia and the Pacific -- Chapter 15: Foreign Direct Investment and the Poverty Reduction Nexus in Southeast Asia.s
Keywords: Development economics; Economic policy; Social policy; Climatology; Development Economics; Economic Policy; Social Policy; Climate Sciences